THE PERFORMANCE ANALYSIS OF IRRIGATION AREA OF CIBENDUNG WEIR OF BREBES REGENCY - Nur Azis Zain; Ohan Farhan (FAKULTAS TEKNNIK UNIVERSITAS SWADAYA GUNUNG JATI, 2018)
Cibendung Weir comprised in the district of Banjarharjo Brebes Center Java, the located approximately less than 50 km from Cirebon and 40 km from Brebes Center Java, and exist some villages such as, Cikakak, Karang Maja, Tiwulandu Village in East and Tonjong, Singkup, Gandol in West.Cibendung Weir have duct the name is Induk Cibendung Weir or named D.I Jangkelok Hilir. At first, the water able to dilute more less 6677ha but in this time only more less 6349ha, the trouble is diversion of the use of land. This Cibendung Weir was built in the years 1901 – 1904. The irrigation areas of Cibendung Weir supply six kemantren such as Kemantren Cibendung, Kemantren Bantarsari, Kemantren Losari Hulu, Kemantren Losari Hilir, Kemantren Kubangjero, and Kemantren Rungkang.The purpose of this research is become reference from evaluation performance of the irrigation area in Cibendung Weir by analyzing the physical condition of building although duct in the irrigation area of Cibendung Weir, analyzing of human resource in the irrigation area of Cibendung Weir, analyzing of rain Hydrology in the irrigation area of Cibendung Weir, analyzing of income from Bendung Cibendong, analyzing of the patterns plants in the irrigation area of Cibendung Weir, and analyzing planning plant and the realization of planting in the irrigation area of Cibendung Weir.The method of this research is qualitative method, in which the fission of the problem is explained that subject or the object research based on the facts which used during doing the research in performance of irrigation system and try to make a good relation in deep from the aspects particularly.Based on the build condition in this irrigation area is classified as satisfactory with percentage of damage reached 11,30%. Meanwhile, the duct condition in this irrigation area Cibendung Weir is good classified with percentage of damage reached 8,21%. The condition of organizer in DI Jangkelok Cibendung Weir only available 51 people, while in needed is 67 people with less percentage reached 17,94% so that service toward the duct condition is less completed and have the impact to net condition which less wake or always damaged, this situation should be increased.From the results of the analysis of the ratio of demand discharge with available discharge added effective rainfall in Irrigation Area Jengkelok,Cibendung Weir fulfilled,but many unused discharge it is necessary to modify cropping pattern in orde to maximize the potential of available discharge. The planting realization in 7 years ago in the irrigation area Jangkelok Cibendung Weir it is less from the planning plant, but in the period of 2011/2012 occurs increased 7,34% and the realization of intensity planting is average 243,77% while the average of planning plan is 268,91% thus the lower plant in productivity in this case since it can’t be done to planting in this wide area.